Cardiorespiratory fitness and nutritional status of schoolchildren: 30-year evolution - Gerson Luis de Moraes Ferrari; Mario Maia Bracco; Victor K. Rodrigues Matsudo; Mauro Fisberg (Elsevier, 2013)
Objective: To compare the changes in cardiorespiratory fitness in evaluations performed every ten years since 1978/1980, according to the nutritional status and gender of students in the city of Ilhabela, Brazil. Methods: The study is part of the Mixed Longitudinal Project on Growth, Development and Physical Fitness of Ilhabela. The study included 1,291 students of both genders, aged 10 to 11 years old. The study periods were: 1978/1980, 1988/1990, 1998/2000, and 2008/2010. The variables analyzed were: body weight, height, and cardiorespiratory fitness (VO2max - L.min-1 and mL.kg-1.min-1) performed using a submaximal progressive protocol on a cycle ergometer. Individuals were classified as normal weight and overweight according to curves proposed by the World Health Organization of body mass index for age and gender. Analysis of variance (ANOVA) with three factors followed by the Bonferroni method were used to compare the periods. Results: The number of normal weight individuals (61%) was higher than that of overweight. There was a significant decrease in cardiorespiratory fitness in both genders. Among the schoolchildren with normal weight, there was a decrease of 22% in males and 26% in females. In overweight schoolchildren, males showed a decrease of 12.7% and females, of 18%. Conclusion: During a 30-year analysis with reviews every ten years from 1978/1980, there was a significant decrease in cardiorespiratory fitness in schoolchildren of both genders, which cannot be explained by the nutritional status. The decline in cardiorespiratory fitness was greater in individuals with normal weight than in overweight individuals. Resumo: Objetivo: Comparar as mudanças da aptidão cardiorrespiratória em avaliações a cada 10 anos a partir de 1978/1980, de acordo com o estado nutricional e o sexo de escolares do município de Ilhabela, Brasil. Métodos: O estudo faz parte do Projeto Misto-Longitudinal de Crescimento, Desenvolvimento e Aptidão Física de Ilhabela. Participaram do estudo 1.291 escolares de ambos os sexos, de 10 e 11 anos de idade. Os períodos analisados foram 1978/1980, 1988/1990, 1998/2000 e 2008/2010. As variáveis analisadas foram peso corporal, estatura e aptidão cardiorrespiratória (VO2máx - L.min−1 e mL.kg−1.min−1) realizada por um protocolo progressivo submáximo em um ciclo ergômetro. Os indivíduos foram classificados em eutróficos e excesso de peso mediante as curvas propostas pela Organização Mundial da Saúde de índice de massa corporal para idade e sexo. Para comparar os períodos, foi utilizado a ANOVA com três fatores, seguida pelo método Bonferroni. Resultados: A quantidade de eutróficos (61%) foi maior do que a de excesso de peso. Houve diminuição significativa da aptidão cardiorrespiratória em ambos os sexos. Entre os escolares meninos e as meninas eutróficas houve diminuição de 22% e 26%, respectivamente. Nos escolares com excesso de peso, os meninos diminuíram em 12,7%, e as meninas, em 18%. Conclusão: Em uma análise de 30 anos, com avaliações a cada 10 anos a partir de 1978/1980, houve uma diminuição significante da aptidão cardiorrespiratória em escolares de ambos os sexos, que não pode ser explicada pelo estado nutricional. A queda da aptidão cardiorrespiratória foi maior nos escolares eutróficos do que nos obesos. Keywords: Nutritional status, Physical fitness, Physical activity, Aerobic exercise, Palavras-chave: Estado nutricional, Aptidão física, Atividade física, Exercício aeróbico